Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00384-012-1490-y
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity related to defunctioning loop ileostomy in low anterior resection

Abstract: This study indicates high morbidity associated with defunctioning loop ileostomy. Our data suggest that the stoma time should be limited to reduce complications. Monitoring and early stoma reversal should be considered in elderly patients. Furthermore, stoma reversal is not uneventful, and more studies are needed to address how to minimize complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 23 publications
4
75
1
Order By: Relevance
“…Available literature shows the formation of a defunctioning stoma to carry morbidity in the early postoperative period [32, 33] and to extend postoperative hospital stay [34], mirroring our findings; however, the presence of a defunctioning stoma being associated with delay to adjuvant therapy has not been previously documented. The use of a defunctioning stoma is commonly associated with patients who have undergone preoperative chemoradiotherapy, rectal resections, and major or difficult resections, factors which may represent the cause of delay as opposed to the presence of a stoma.…”
Section: Discussionsupporting
confidence: 86%
“…Available literature shows the formation of a defunctioning stoma to carry morbidity in the early postoperative period [32, 33] and to extend postoperative hospital stay [34], mirroring our findings; however, the presence of a defunctioning stoma being associated with delay to adjuvant therapy has not been previously documented. The use of a defunctioning stoma is commonly associated with patients who have undergone preoperative chemoradiotherapy, rectal resections, and major or difficult resections, factors which may represent the cause of delay as opposed to the presence of a stoma.…”
Section: Discussionsupporting
confidence: 86%
“…Patients receiving neoadjuvant therapy generally have reversal of their ileostomies postponed until adjuvant chemotherapy is completed; this would account for the difference existing between groups. Several studies have suggested that ileostomy closure before adjuvant chemotherapy may be beneficial in improving chemotherapy delivery; however, concerns remain regarding the impact post ileostomy closure complications may have on the timely administration of adjuvant chemotherapy [5,13,27,33]. Such concerns appear valid, given the increased wound infection rates associated with early closure.…”
Section: Discussionmentioning
confidence: 92%
“…Obviously, AL rates are only calculated for patients in whom an anastomosis has been created. Therefore hospitals with lower rates of patients with anastomoses could automatically have better scores without providing better quality of care, as the stoma itself may cause morbidity, lead to increased readmissions51 52 and may be associated with morbidity at the time of surgical removal of the stoma 53. In reality, there is probably an optimum percentage of defunctioning stomas and end colostomies to be constructed, and AL rates should always be seen in the light of these percentages.…”
Section: Discussionmentioning
confidence: 99%